A study on the evaluation of bite force, prosthetic and nutritional status in adult cleft patients in Kolkata - Alak Kumar Bera; Samiran Das; Jayanta Bhattacharyya; Sayan Majumdar; Saumitra Ghosh; Preeti Goel (Wolters Kluwer Medknow Publications, 2018)
Context: Altered orofacial morphology and poor dental status affects the dietary intake of cleft patient, making susceptible to nutritional imbalance. Oral health care planning for this population is impossible without the evaluation of stomatognathic functional status as well as prosthetic and nutritional status and need. Aims: The aim of this study was to evaluate prosthetic status and prosthetic treatment need, bite force and nutritional status, in adult cleft patients and to compare them with the adult noncleft population of similar definition. Settings and Design: Cleft (n = 250) and noncleft (n = 250) individuals of either sex, aged 18 years or above, excluding severe medically compromised and differently abled, were examined and individual biteforce was measured after obtaining written consent and ethical clearance from the two institutions in Kolkata. Subjects and Methods: A "raw data sheet" was prepared according to the parameters of the "Oral Health Surveys: Basic methods," World Health Organization (1997) for evaluation of prosthetic status and need, dentition status and Mini-Nutritional Assessment, Nestlé (1994) for the evaluation nutritional status. A Gnathodynamometer was used to record bite force. Statistical Analysis Used: Statistical analysis was performed using SPSS 20.0.1, Graph Pad Prism version 5, Student's t-test, and Chi-square test. Results: The mean bite force of frontal area in cleft group (3.4356 ± 0.9457 kgf) was found to be significantly lower (P < 0.0001) than in noncleft (22.8749 ± 5.3644 kgf) group. The difference of mean bite force in the right side (2.4576 ± 0.6131 kgf) and left side (1.2708 ± 0.1036 kgf) in cleft group was found to be statistically significant (P < 0.0001). Prosthetic need in maxillary arch was found to be significantly (χ2: 490.0000; P < 0.0001) higher in cleft than in noncleft group. Nutritional status was observed to be significantly (χ2: 179.4049; P < 0.0001) higher "at risk" in cleft than in noncleft group. Conclusions: Lack of adequate Government concern leading to significantly higher prosthetic need and lower prosthetic status, hence lower bite force resulting lower nutritional status in adult cleft patients in Kolkata.